THE EFFECT OF RAMBUTAN PEEL EXTRACT (NEPHELIUM LAPPACEUM L) TO TOTAL LEUKOCYTES AND HISTOPATHOLOGICAL OF RAT LUNGS EXPOSED BY CIGARETTE SMOKE - Lisdiana, Lisdiana; WH, Nugrahaningsih; Widyaningrum, Priyantini (Universitas Negeri Semarang, 2017)
Cigarette smoke is one of exogenous free radicals sources. When it is inhaled, its activity may damage the structure of lung function. The impacts of free radicals can be reduced through the provision of antioxidants. Rambutan fruit peel contains phenolic compound in the form of polyphenols that are antioxidants.The purpose of this study is to determine the effect of rambutan fruit peel extracts to the number of leukosit and lung structure on rats exposed by cigarette smoke. The research design used Post Test Control Group Design. A sample of 25 rats were divided into 5 groups, each group consisting of 5 rats. The positive control group (K +) were given a standard food and drinking water, the negative control group (K) by 3 cigarettes, the treatment groups (KP1, KP2, KP3) by 3 cigarettes and peel extract of rambutan each treatment group with a dose 15 mg/kg, 30 mg/kg and 45 mg/kg for 30 days. Total leukocyt measured by Auto Hematology Analyzer Mindray BC 2800vet. Total leukocytes and the damage of the lung were tested by one- way ANOVA. The number of leukocytes and damage to the lungs was analyzed by one-way ANOVA. and further tested with LSD. Next, the effective dose was tested by using linear regression. The result has shown that the average of total leukocytes in K+, K-, KP1, KP2, and KP3 was 6.28 x103/µl, 11.98 x103/µl, 9.88 x103/µl, 8.48 x103/µl, and 7.72 x103/µl respectively. Based on ANOVA, the rats have been exposed to cigarette smoke and given the extract of rambutan peel underwent decreasing total leukocytes and decreasing damage on alveolus more significant than those which has been exposed to cigarette smoke with no extract of rambutan peel. The effective dose of the extract of rambutan peel that was foun d to decrease total leukocytes and to protect the damage of the lung caused by cigarette smoke was 45 mg/kg body weight. Conclusion: the extract of rambutan peel was able to decrease the total leukocytes and protect the histopathological of rat lung that has been exposed to cigarette smoke.